Habitação e modernização: Cidade Nova e maneiras de viver em Natal no início do século XX - Costa, Ricardo José Vilar da (2008)
Analyses the presence of new standards of habitation detected in the construction of the region called Cidade Nova, in the first s years of the XX century. Associates the presence of these new patterns with the historical moment lived by the capital, marked by the urban modernization and by the changes of local life. Map voices that, introduced by the republican groups since 1889, pronounced the overcome of the old city of the XIX century asseverated a new model of town. Make use, as fundamental fonts of research, of the urban chronicles produced by the local intellectuals and the newspapers, like A República. Dialog with chronics that includes since propositions about the colonial past until the preoccupations about the acting of the State on how to order the public space. Identifies on those texts the political motivations and the elements whose where inherent to capitalism that accelerated the changes occurred in the urban space. Demonstrates the gradual occupation of Cidade Nova as an important modification happened in the city from that time on. That neighborhood adopted a new model on how to construct the houses of their citizens and helped to promote the urban life as a whole. From now on, Natal has a space meant for the home of their richest families. Recognizes, from many ways, many discourses, manners of living that was legitimized by the changing of the XIX to the XX century and has his highest point in the 1920´s. And it was representative of the strong attachment about the habits of refinery and order in the essence of the private life of the local urban elites